2010
DOI: 10.1590/s0100-69912010000500009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso tópico do metronidazol no processo de cicatrização de feridas: um estudo experimental

Abstract: Metronidazole 4% solution at a dose of 50 mg/kg applied topically to wounds healing by secondary intention facilitates early peripheral epithelialization, does not interfere with wound contraction and delays the appearance of myofibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
8
0
2
Order By: Relevance
“…It has been used systemically and/or topically to treat wound infections, for example, fungating carcinomas and necrotic pressure ulcers [45,46], because of its ability to reduce the malodor of anaerobically colonized wounds (malodorous wounds). Moreover, two studies suggested that topical metronidazole increased epithelialization during wound healing by secondary intention in rats [47,48]. However, most treatments use conventional gel preparations for MZ, which require generous application and need a secondary dressing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used systemically and/or topically to treat wound infections, for example, fungating carcinomas and necrotic pressure ulcers [45,46], because of its ability to reduce the malodor of anaerobically colonized wounds (malodorous wounds). Moreover, two studies suggested that topical metronidazole increased epithelialization during wound healing by secondary intention in rats [47,48]. However, most treatments use conventional gel preparations for MZ, which require generous application and need a secondary dressing.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that evaluated the chondrocyte proliferation activity by the expression of cellular proliferation nuclear antigen in the zone of cartilage growth after 30 days of subtotal 5/6 nephrectomy in rats, it was possible to conclude that the number of proliferating cells in the growth plateau was significantly lower in uremic rats when compared to control rats 1 . Another experimental study in rats that investigated the density of myofibroblasts in wound healing by the same method employed in this study concluded that metronidazole, applied topically to wound healing with second intention, does not interfere with the contraction of the wound and delays the appearance of myofibroblasts 32 .…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, the tissue densities of myofibroblasts did not differ between the arginine and control groups (p=0.0511), although there was a numerical difference. An experimental study in rats that investigated the density of myofibroblasts in wound healing by the same method employed here concluded that metronidazole, applied topically to wounds with secondary intention healing, does not interfere with wound contraction and delays the appearance of myofibroblasts 23 .…”
Section: Figure 2 Comparison Between the Mean Percentages Of Collagementioning
confidence: 78%